Consideraciones sobre el tratamiento de la osteomielitis - Valls, José (1937)
The authors leave it established that up to the present time no method has been resolved which yields to obtain absolute sterilization of the infectious focus in bone. They say : it is known when an Osteomyelitis begins but it is absolutely unknown when it ends. They have utilized the surgical treatment in acute cases, varying the technic according to cases. 1st The drainage of the subperiosteal abscess. 2nd The trephination (trephining). 3rd The diaphysic resection. The surgical treatment having been realized once, they resorted to immovilization by plaster, according to Orr’s method. They have much confidence in Orr’s method in chronic cases, but not in acute cases, as the results are not so uniform. They add to the surgical treatment of acute osteomyelitis, vaccinetherapy, serotherapy, quinin etheraphy and the bacteriophage by endovenous route, and as coadjuvaut they have utilized with beneficial results blood transfusions during the post-operative period. They establish that in chronic osteomyelitis free and ample opening and the removal of necrosed fragments of bone as an operation of necessity. The devoted, ad vocates of the method of Orr state that they have no experience with Ball’s method. The diaphysic resection which they have done in 4 cases gave very poor results. They have resorted to several cases of amputations in the acute period, amongst adult patients, after having ezhausted all medical and surgical mesures without any local improvement and with aggravation of the general state of the patient, to which they justify their action.